```Sums of the form X^A + Y^B + Z^C for
each total in the range -100 to +100.

X^A +   Y^B +  Z^C =    N
----    ----   ----   ----
3^2 +  -5^3 +  2^4 = -100
5^2 +  -5^3 +  1^4 =  -99
9^2 +   4^3 + -3^5 =  -98
-4^3 +  -2^5 + -1^7 =  -97
0^2 +  -4^3 + -2^5 =  -96
1^2 +  -4^3 + -2^5 =  -95
-5^3 +   2^5 + -1^7 =  -94
4^2 +  -5^3 +  2^4 =  -93
2^2 +  -4^3 + -2^5 =  -92
6^2 +   1^3 + -2^7 =  -91
6^2 +  -5^3 + -1^5 =  -90
6^2 +  -5^3 +  0^4 =  -89
6^2 +  -5^3 +  1^4 =  -88
3^2 +  -4^3 + -2^5 =  -87
7^2 +  -6^3 +  3^4 =  -86
4^2 +   3^3 + -2^7 =  -85
5^2 +  -5^3 +  2^4 =  -84
12^2 +   2^4 + -3^5 =  -83
6^2 +   5^3 + -3^5 =  -82
9^2 +   3^4 + -3^5 =  -81
4^2 +  -4^3 + -2^5 =  -80
7^2 +   0^3 + -2^7 =  -79
7^2 +   1^3 + -2^7 =  -78
4^2 +  -5^3 +  2^5 =  -77
7^2 +  -5^3 +  0^4 =  -76
7^2 +  -5^3 +  1^4 =  -75
9^2 +  -3^3 + -2^7 =  -74
6^2 +  -5^3 +  2^4 =  -73
8^2 +  -2^3 + -2^7 =  -72
5^2 +  -4^3 + -2^5 =  -71
19^2 +  -8^3 +  3^4 =  -70
3^3 +   2^5 + -2^7 =  -69
5^2 +  -5^3 +  2^5 =  -68
36^2 + -11^3 + -2^5 =  -67
-4^3 +  -1^5 + -1^7 =  -66
0^2 +  -4^3 + -1^5 =  -65
0^2 +  -4^3 +  0^4 =  -64
0^2 +  -4^3 +  1^4 =  -63
1^2 +  -4^3 +  1^4 =  -62
2^2 +  -4^3 + -1^5 =  -61
-3^3 +  -2^5 + -1^7 =  -60
0^2 +  -3^3 + -2^5 =  -59
1^2 +  -3^3 + -2^5 =  -58
6^2 +  -5^3 +  2^5 =  -57
3^2 +  -4^3 + -1^5 =  -56
2^2 +  -3^3 + -2^5 =  -55
3^2 +  -4^3 +  1^4 =  -54
17^2 +  -7^3 +  1^4 =  -53
3^2 +  -5^3 +  2^6 =  -52
8^2 +  -3^5 +  2^7 =  -51
3^2 +  -3^3 + -2^5 =  -50
4^2 +  -4^3 + -1^5 =  -49
0^2 +  -4^3 +  2^4 =  -48
1^2 +  -4^3 +  2^4 =  -47
9^2 +   1^3 + -2^7 =  -46
8^2 +  -5^3 +  2^4 =  -45
2^2 +  -4^3 +  2^4 =  -44
4^2 +  -3^3 + -2^5 =  -43
35^2 + -11^3 +  2^6 =  -42
-2^3 +  -2^5 + -1^7 =  -41
0^2 +  -2^3 + -2^5 =  -40
1^2 +  -2^3 + -2^5 =  -39
5^2 +  -4^3 +  1^4 =  -38
8^2 +   3^3 + -2^7 =  -37
2^2 +  -2^3 + -2^5 =  -36
3^2 +  -5^3 +  3^4 =  -35
-1^3 +  -2^5 + -1^7 =  -34
0^2 +  -1^3 + -2^5 =  -33
0^2 +   0^3 + -2^5 =  -32
0^2 +   1^3 + -2^5 =  -31
1^2 +   1^3 + -2^5 =  -30
-3^3 +  -1^5 + -1^7 =  -29
0^2 +  -3^3 + -1^5 =  -28
0^2 +  -3^3 +  0^4 =  -27
0^2 +  -3^3 +  1^4 =  -26
1^2 +  -3^3 +  1^4 =  -25
2^2 +  -3^3 + -1^5 =  -24
2^2 +  -3^3 +  0^4 =  -23
2^2 +  -3^3 +  1^4 =  -22
14^2 +  -6^3 + -1^5 =  -21
2^2 +   2^3 + -2^5 =  -20
3^2 +  -3^3 + -1^5 =  -19
3^2 +  -3^3 +  0^4 =  -18
3^2 +  -3^3 +  1^4 =  -17
4^2 +   0^3 + -2^5 =  -16
3^2 +   2^3 + -2^5 =  -15
7^2 +  -4^3 +  1^4 =  -14
12^2 +  -5^3 + -2^5 =  -13
4^2 +  -3^3 + -1^5 =  -12
0^2 +  -3^3 +  2^4 =  -11
-2^3 +  -1^5 + -1^7 =  -10
0^2 +  -2^3 + -1^5 =   -9
0^2 +  -2^3 +  0^4 =   -8
0^2 +  -2^3 +  1^4 =   -7
1^2 +  -2^3 +  1^4 =   -6
2^2 +  -2^3 + -1^5 =   -5
2^2 +  -2^3 +  0^4 =   -4
-1^3 +  -1^5 + -1^7 =   -3
0^2 +  -1^3 + -1^5 =   -2
0^2 +  -1^3 +  0^4 =   -1
0^2 +   0^3 +  0^4 =    0
0^2 +   0^3 +  1^4 =    1
0^2 +   1^3 +  1^4 =    2
1^2 +   1^3 +  1^4 =    3
2^2 +   0^3 +  0^4 =    4
2^2 +   0^3 +  1^4 =    5
2^2 +   1^3 +  1^4 =    6
0^2 +   2^3 + -1^5 =    7
0^2 +   2^3 +  0^4 =    8
0^2 +   2^3 +  1^4 =    9
1^2 +   2^3 +  1^4 =   10
3^2 +   1^3 +  1^4 =   11
2^2 +   2^3 +  0^4 =   12
2^2 +   2^3 +  1^4 =   13
4^2 +  -1^3 + -1^5 =   14
0^2 +  -1^3 +  2^4 =   15
0^2 +   0^3 +  2^4 =   16
0^2 +   1^3 +  2^4 =   17
1^2 +   1^3 +  2^4 =   18
2^2 +  -1^3 +  2^4 =   19
2^2 +   0^3 +  2^4 =   20
2^2 +   1^3 +  2^4 =   21
7^2 +  -3^3 +  0^4 =   22
4^2 +   2^3 + -1^5 =   23
0^2 +   2^3 +  2^4 =   24
1^2 +   2^3 +  2^4 =   25
3^2 +   1^3 +  2^4 =   26
0^2 +   3^3 +  0^4 =   27
0^2 +   3^3 +  1^4 =   28
1^2 +   3^3 +  1^4 =   29
2^2 +   3^3 + -1^5 =   30
2^2 +   3^3 +  0^4 =   31
2^2 +   3^3 +  1^4 =   32
3^2 +   2^3 +  2^4 =   33
5^2 +   2^3 +  1^4 =   34
6^2 +  -1^3 +  0^4 =   35
3^2 +   3^3 +  0^4 =   36
3^2 +   3^3 +  1^4 =   37
6^2 +   1^3 +  1^4 =   38
2^3 +   2^5 + -1^7 =   39
4^2 +   2^3 +  2^4 =   40
5^2 +   0^3 +  2^4 =   41
5^2 +   1^3 +  2^4 =   42
0^2 +   3^3 +  2^4 =   43
1^2 +   3^3 +  2^4 =   44
6^2 +   2^3 +  1^4 =   45
3^2 +  -3^3 +  2^6 =   46
2^2 +   3^3 +  2^4 =   47
4^2 +   0^3 +  2^5 =   48
5^2 +   2^3 +  2^4 =   49
7^2 +   0^3 +  1^4 =   50
7^2 +   1^3 +  1^4 =   51
3^2 +   3^3 +  2^4 =   52
5^2 +   3^3 +  1^4 =   53
0^2 +  -3^3 +  3^4 =   54
8^2 +  -2^3 + -1^5 =   55
4^2 +   2^3 +  2^5 =   56
7^2 +   2^3 +  0^4 =   57
7^2 +   2^3 +  1^4 =   58
4^2 +   3^3 +  2^4 =   59
6^2 +   2^3 +  2^4 =   60
8^2 +   5^3 + -2^7 =   61
6^2 +   3^3 + -1^5 =   62
6^2 +   3^3 +  0^4 =   63
0^2 +   4^3 +  0^4 =   64
0^2 +   4^3 +  1^4 =   65
1^2 +   4^3 +  1^4 =   66
2^2 +   4^3 + -1^5 =   67
2^2 +   4^3 +  0^4 =   68
2^2 +   4^3 +  1^4 =   69
4^2 +  -3^3 +  3^4 =   70
8^2 +   2^3 + -1^5 =   71
8^2 +   2^3 +  0^4 =   72
3^2 +   4^3 +  0^4 =   73
3^2 +   4^3 +  1^4 =   74
4^2 +   3^3 +  2^5 =   75
7^2 +   3^3 +  0^4 =   76
7^2 +   3^3 +  1^4 =   77
9^2 +   5^3 + -2^7 =   78
6^2 +   3^3 +  2^4 =   79
0^2 +   4^3 +  2^4 =   80
0^2 +   0^3 +  3^4 =   81
0^2 +   1^3 +  3^4 =   82
1^2 +   1^3 +  3^4 =   83
2^2 +   4^3 +  2^4 =   84
2^2 +   0^3 +  3^4 =   85
2^2 +   1^3 +  3^4 =   86
14^2 +  -5^3 +  2^4 =   87
8^2 +   2^3 +  2^4 =   88
0^2 +   2^3 +  3^4 =   89
1^2 +   2^3 +  3^4 =   90
3^2 +   1^3 +  3^4 =   91
7^2 +   3^3 +  2^4 =   92
2^2 +   2^3 +  3^4 =   93
11^2 +  -3^3 +  0^4 =   94
6^2 +   3^3 +  2^5 =   95
4^2 +   4^3 +  2^4 =   96
4^2 +   0^3 +  3^4 =   97
3^2 +   2^3 +  3^4 =   98
10^2 +  -1^3 +  0^4 =   99
6^2 +   4^3 +  0^4 =  100
```
Frank Rubin May 14, 2003